The diet‐derived short chain fatty acid propionate improves beta‐cell function in humans and stimulates insulin secretion from human islets in vitro. Issue 2 (23rd November 2016) - Pingitore, Attilio; Chambers, Edward S.; Hill, Thomas; Maldonado, Inmaculada Ruz; Liu, Bo; Bewick, Gavin; Morrison, Douglas J.; Preston, Tom; Wallis, Gareth A.; Tedford, Catriona; Castañera González, Ramón; Huang, Guo C.; et al.
Abstract : Aims: Diet‐derived short chain fatty acids (SCFAs) improve glucose homeostasis in vivo, but the role of individual SCFAs and their mechanisms of action have not been defined. This study evaluated the effects of increasing colonic delivery of the SCFA propionate on β‐cell function in humans and the direct effects of propionate on isolated human islets in vitro. Materials and methods: For 24 weeks human subjects ingested an inulin‐propionate ester that delivers propionate to the colon. Acute insulin, GLP‐1 and non‐esterified fatty acid (NEFA) levels were quantified pre‐ and post‐supplementation in response to a mixed meal test. Expression of the SCFA receptor FFAR2 in human islets was determined by western blotting and immunohistochemistry. Dynamic insulin secretion from perifused human islets was quantified by radioimmunoassay and islet apoptosis was determined by quantification of caspase 3/7 activities. Results: Colonic propionate delivery in vivo was associated with improved β‐cell function with increased insulin secretion that was independent of changes in GLP‐1 levels. Human islet β‐cells expressed FFAR2 and propionate potentiated dynamic glucose‐stimulated insulin secretion in vitro, an effect that was dependent on signalling via protein kinase C. Propionate also protected human islets from apoptosis induced by the NEFA sodium palmitate and inflammatory cytokines. Conclusions: Our results indicate that propionate has beneficial effects on β‐cell function in vivo, and in vitro analyses demonstrated that it has direct effects to potentiate glucose‐stimulated insulin release and maintain β‐cell mass through inhibition of apoptosis. These observations support ingestion of propiogenic dietary fibres to maintain healthy glucose homeostasis.